How international experience helps shape labor market outcomes - Carl Davidson; Fredrik Heyman; Steven J. Matusz; Fredrik Sjöholm; Susan Chun Zhu (Research Institute of Industrial Economics (IFN), 2022)
This paper examines how experience from working in a foreign owned firm affects worker mobility. International experience can provide a worker with knowledge about foreign operations, thereby making them more attractive to other employers who are also engaged in international businesses. We follow workers in local Swedish firms where some experience an internationalization shock when their firm is acquired by a foreign multinational firm. Matching acquired firms with a group of similar control firms and applying a stacked difference-in-differences estimation approach, we find that international experience increases the likelihood of job switching to a multinational firm by around 4 percentage points and decreases the likelihood of job switching to a local firm by around 5 percentage points. Moreover, the post-acquisition wage growth rate is 10 percentage points higher for workers moving to MNEs as compared to stayers at acquired firms, leading to a steeper wage growth trajectory for movers to MNEs.
Keywords: F16; F66; J60; 330; Globalization; Multinational firms; FDI; Job mobility